Efficient CO2 Removal for Ultra‐Pure CO Production by Two Hybrid Ultramicroporous Materials. (22nd February 2018) - Chen, Kai‐Jie; Yang, Qing‐Yuan; Sen, Susan; Madden, David G.; Kumar, Amrit; Pham, Tony; Forrest, Katherine A.; Hosono, Nobuhiko; Space, Brian; Kitagawa, Susumu; Zaworotko, Michael J.
Abstract: Removal of CO2 from CO gas mixtures is a necessary but challenging step during production of ultra‐pure CO as processed from either steam reforming of hydrocarbons or CO2 reduction. Herein, two hybrid ultramicroporous materials (HUMs), SIFSIX‐3‐Ni andTIFSIX‐2‐Cu‐i, which are known to exhibit strong affinity for CO2, were examined with respect to their performance for this separation. The single‐gas CO sorption isotherms of these HUMs were measured for the first time and are indicative of weak affinity for CO and benchmark CO2 /CO selectivity (>4000 forSIFSIX‐3‐Ni ). This prompted us to conduct dynamic breakthrough experiments and compare performance with other porous materials. Ultra‐pure CO (99.99 %) was thereby obtained from CO gas mixtures containing both trace (1 %) and bulk (50 %) levels of CO2 in a one‐step physisorption‐based separation process.